How adverse are Mediterranean waters to the deep-sea fauna? A study of the Gibraltar exchange based on Mollusca from the “BALGIM” expedition - Utrilla O; Gofas S; Salas C (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Late Pleistocene boreal molluscs in the Gulf of Cadiz: Past and current oceanographic implications - J. Urra; O. Utrilla; S. Gofas; V.A. Valencia; C. Farias; E. González-García; N. López-González; L.M. Fernández-Salas; J.L. Rueda (Quaternary Science Reviews, 2023)

Seasonality and trophic diversity in molluscan assemblages from the Bay of Tunis (southern Mediterranean Sea) - M. ANTIT; A. DAOULATLI; J. URRA; J. L. RUEDA; S. GOFAS; C. SALAS (Mediterranean Marine Science, 2016)
Soft bottom molluscan assemblages from the Bay of Tunis have been studied in order to analyse their seasonality and trophic diversity in relation to environmental variables. A total of 147 species of molluscs was identified, with gastropods displaying the highest species richness and bivalves the highest abundances, and including five non-indigenous species such as the dominant ectoparasite Polycerella emertoni. Carnivorous and scavenger gastropods were among the most frequent species, reflecting a diverse benthic community. Seasonal changes were significant, being more acute at 3-4 m than at 10-15 m depth, and were driven mainly by seawater temperature and percentage of organic matter in the sediment. The high affluence of tourists in summer was coincident with high decreases in species richness and abundance of molluscs, together with a strong siltation of the sediment. Nevertheless, most trophic groups remained and the trophic diversity was relatively high. Significant relationships were found between the index of trophic diversity and Shannon-Wiener diversity and evenness indices, suggesting that the identity of the species with its particular trophic trait, together with the good distribution of the individuals among the species (density) would be the drivers for the maintenance of the molluscan food web under environmental stress. The abundance of P. emertoni altered the trophic structure of the molluscan assemblage, with the ectoparasite trophic group reaching an unusual punctual higher dominance. Soft bottom molluscan assemblages of the Bay of Tunis should be taken into account in monitoring programs for anthropogenic impacts and non-indigenous species trends throughout the Mediterranean basin.

Alien species in the Mediterranean Sea by 2012. A contribution to the application of European Union’s Marine Strategy Framework Directive (MSFD). Part 2. Introduction trends and pathways - Α. ZENETOS; S. GOFAS; C. MORRI; A. ROSSO; D. VIOLANTI; J.E. GARCIA RASO; M.E. CINAR; A. ALMOGI-LABIN; A.S. ATES; E. AZZURRO; E. BALLESTEROS; C.N. BIANCHI; et al. (Mediterranean Marine Science, 2012)
More than 60 marine non-indigenous species (NIS) have been removed from previous lists and 84 species have been added, bringing the total to 986 alien species in the Mediterranean [775 in the eastern Mediterranean (EMED), 249 in the central Mediterranean (CMED), 190 in the Adriatic Sea (ADRIA) and 308 in the western Mediterranean (WMED)]. There were 48 new entries since 2011 which can be interpreted as approximately one new entry every two weeks. The number of alien species continues to increase, by 2-3 species per year for macrophytes, molluscs and polychaetes, 3-4 species per year for crustaceans, and 6 species per year for fish. The dominant group among alien species is molluscs (with 215 species), followed by crustaceans (159) and polychaetes (132). Macrophytes are the leading group of NIS in the ADRIA and the WMED, reaching 26-30% of all aliens, whereas in the EMED they barely constitute 10% of the introductions. In the EMED, molluscs are the most species-rich group, followed by crustaceans, fish and polychaetes. More than half (54%) of the marine alien species in the Mediterranean were probably introduced by corridors (mainly Suez). Shipping is blamed directly for the introduction of only 12 species, whereas it is assumed to be the most likely pathway of introduction (via ballasts or fouling) of another 300 species. For approximately 100 species shipping is a probable pathway along with the Suez Canal and/or aquaculture. Approximately 20 species have been introduced with certainty via aquaculture, while >50 species (mostly macroalgae), occurring in the vicinity of oyster farms, are assumed to be introduced accidentally as contaminants of imported species. A total of 18 species are assumed to have been introduced by the aquarium trade. Lessepsian species decline westwards, while the reverse pattern is evident for ship-mediated species and for those introduced with aquaculture. There is an increasing trend in new introductions via the Suez Canal and via shipping.

New records of recently described chemosymbiotic bivalves for mud volcanoes within the European waters (Gulf of Cádiz) - J.L. RUEDA; J. URRA; S. GOFAS; N. LOPEZ-GONZALEZ; L.M. FERNANDEZ-SALAS; V. DIAZ-DEL-RIO (Mediterranean Marine Science, 2012)
Chemosymbiotic bivalves are important members of cold seep communities and information on their distribution in theEuropean waters is still quite scarce. This study reports the presence of living populations and shell remains of some recently described bivalves such as Lucinoma asapheus, Solemya elarraichensis and Acharax gadirae as well as Bathymodiolus sp. in the mud volcanoes of the Spanish Atlantic waters. Living populations of these species were thus far only found in Anastasya, Aveiro and Almazán mud volcanoes, together with other chemosymbiotic metazoa (Siboglinum spp.), suggesting the presence of moderate seepage activity. In other mud volcanoes (Albolote, Gazul), the benthic communities are dominated by sessile filter feeders on authigenic carbonates (chimneys, slabs) and only the shell remains of some chemosymbiotic bivalves were found, indicating earlier or very low seepage conditions. The present study elaborates on the known distribution of L. asapheus and S. elarraichensis to the European waters of the Gulf of Cádiz.

Errata to the Review Article (Medit. Mar. Sci. 11/2, 2010, 381-493): "Alien species in the Mediterranean Sea by 2010. A contribution to the application of European Union’s Marine Strategy Framework Directive (MSFD). Part I. Spatial distribution" - A. ZENETOS; S. GOFAS; M. VERLAQUE; M.E. CINAR; J.E GARCIA RASO; C.N. BIANCHI; C. MORRI; E. AZZURRO; M. BILECENOGLU; C. FROGLIA; I. SIOKOU; D. VIOLANTI; et al. (Mediterranean Marine Science, 2011)
The state-of-art on alien species in the Mediterranean Sea is presented, making distinctions among the four subregions defined in the EU Marine Strategy Framework Directive: (i) the Western Mediterranean Sea (WMED); (ii) the Central Mediterranean Sea (CMED); (iii) the Adriatic Sea (ADRIA); and (iv) the Eastern Mediterranean Sea (EMED). The updated checklist (December 2010) of marine alien species within each subregion, along with their acclimatization status and origin, is provided. A total of 955 alien species is known in the Mediterranean, the vast majority of them having being introduced in the EMED (718), less in the WMED (328) and CMED (267) and least in the Adriatic (171). Of these, 535 species (56%) are established in at least one area.Despite the collective effort of experts who attempted in this work, the number of introduced species remains probably underestimated. Excluding microalgae, for which knowledge is still insufficient, aliens have increased the total species richness of the Mediterranean Sea by 5.9%. This figure should not be directly read as an indication of higher biodiversity, as spreading of so many aliens within the basin is possibly causing biotic homogenization. Thermophilic species, i.e. Indo-Pacific, Indian Ocean, Red Sea, Tropical Atlantic, Tropical Pacific, and circum(sub)tropical, account for 88.4% of the introduced species in the EMED, 72.8% in the CMED, 59.3% in the WMED and 56.1% in the Adriatic. Cold water species, i.e. circumboreal, N Atlantic, and N Pacific, make up a small percentage of the introduced species, ranging between 4.2% and 21.6% and being more numerous in the Adriatic and less so in the EMED.Species that are classified as invasive or potentially invasive are 134 in the whole of the Mediterranean: 108 are present in the EMED, 76 in the CMED, 53 in the Adriatic and 64 in the WMED. The WMED hosts most invasive macrophytes, whereas the EMED has the lion’s share in polychaetes, crustaceans, molluscs and fish.

One hundred years after Pinctada: an update on alien Mollusca in Tunisia - M. ANTIT; S. GOFAS; C. SALAS; A. AZZOUNA (Mediterranean Marine Science, 2011)
The occurrences of non-indigenous marine molluscs in Tunisia are reviewed, based booth on a literature survey and on original material. Species are accepted as established if there are two independent reports, either geographically separate or at least one month apart in time. On these grounds, 14 species are accepted (12 alien and 2 expanding their range from elsewhere in the Mediterranean), 3 aliens need confirmation but are likely to meet the standards for acceptation on a short future, and 5 records are rebutted or questioned. Two more species may be considered as cryptogenic, the reports are reliable but it is not clear indication that they are not indigenous. Two of the alien species are reported for the first time in Tunisian waters: the nudibranch Polycerella emertoni qualifies as established, and the bivalve Anadara transversa is tentatively identified from a juvenile live-taken specimen, which awaits further confirmation.The occurrence of aliens in Tunisia is balanced between presumably Lessepsian species of tropical Indo-Pacific origin, and species from other sources including species from the Tropical Atlantic introduced through shipping. Nevertheless there is a prevalence of Lessepsian species towards the Gulf of Gabes in the south, whereas the shipping activity in Tunis harbour may be the main pathway of introduction in the north.

Alien species in the Mediterranean Sea by 2010. A contribution to the application of European Union’s Marine Strategy Framework Directive (MSFD). Part I. Spatial distribution - A. ZENETOS; S. GOFAS; M. VERLAQUE; M.E. CINAR; J.E. GARCIA RASO; C.N. BIANCHI; C. MORRI; E. AZZURRO; M. BILECENOGLU; C. FROGLIA; I. SIOKOU; D. VIOLANTI; et al. (Mediterranean Marine Science, 2010)
The state-of-art on alien species in the Mediterranean Sea is presented, making distinctions among the four subregions defined in the EU Marine Strategy Framework Directive: (i) the Western Mediterranean Sea (WMED); (ii) the Central Mediterranean Sea (CMED); (iii) the Adriatic Sea (ADRIA); and (iv) the Eastern Mediterranean Sea (EMED). The updated checklist (December 2010) of marine alien species within each subregion, along with their acclimatization status and origin, is provided. A total of 955 alien species is known in the Mediterranean, the vast majority of them having being introduced in the EMED (718), less in the WMED (328) and CMED (267) and least in the Adriatic (171). Of these, 535 species (56%) are established in at least one area.Despite the collective effort of experts who attempted in this work, the number of introduced species remains probably underestimated. Excluding microalgae, for which knowledge is still insufficient, aliens have increased the total species richness of the Mediterranean Sea by 5.9%. This figure should not be directly read as an indication of higher biodiversity, as spreading of so many aliens within the basin is possibly causing biotic homogenization. Thermophilic species, i.e. Indo-Pacific, Indian Ocean, Red Sea, Tropical Atlantic, Tropical Pacific, and circum(sub)tropical, account for 88.4% of the introduced species in the EMED, 72.8% in the CMED, 59.3% in the WMED and 56.1% in the Adriatic. Cold water species, i.e. circumboreal, N Atlantic, and N Pacific, make up a small percentage of the introduced species, ranging between 4.2% and 21.6% and being more numerous in the Adriatic and less so in the EMED.Species that are classified as invasive or potentially invasive are 134 in the whole of the Mediterranean: 108 are present in the EMED, 76 in the CMED, 53 in the Adriatic and 64 in the WMED. The WMED hosts most invasive macrophytes, whereas the EMED has the lion’s share in polychaetes, crustaceans, molluscs and fish.

Genetic relationships between marine and marginal-marine populations of Cerithium species from the Mediterranean Sea - M. C. Boisselier-Dubayle; S. Gofas (Marine Biology, 1999)